EFEKTIVITAS PEMBERIAN KOMPOS DAUN SINGKONG (MANIHOT UTILISIMA) TERHADAP PRODUKTIVITAS TANAMAN KACANG TANAH (ARACHIS HYPOGEAL) - Hayati, Faridatul; Mirawati, Baiq; Utami, Septiana Dwi (Jurnal Ilmiah IKIP Mataram, 2020)
This study was aimed to determine the effectiveness of cassava leaf (Manihot Utilisima) as compost to the productivity of peanuts (Arachis hypogeal) as material for making posters. This research was conducted in Jerok Hamlet, Pengembur Village, Pujut Subdistrict, Central Lombok Regency, which was conducted from January to April 2019. The experiment consisted of 4 treatments with 6 replications so that there were 24 number of experimental units with the composition of compost as follows: (K0/control) 1000 gr soil without fertilizer, (K1) 300 gr compost + 700 gr soil, (K2) 500 gr compost + 500 gr soil, (K3) 700 gr compost + 300 gr of soil. Data collecting techniques were carried out by t observation and data obtained were analyzed using Variance Analysis (ANOVA), which was assisted by using the SPSS 15 For Windows program. Result showed that there was no significant effect on the parameters of number of leaves, number of pods, pod wet weight and pod dry weight, but significantly affected on plant height parameters. Statistically there was a tendency for the highest effectiveness in peanut after compost was applied to the K2 treatment. So that the Cassava Leaf (Manihot utilisima) was effective as a fertilizer to peanuts (Arachis hypogeal) height which need to be disseminated to the public using Poster media.